Numerical simulations on self-assembly of polyhedral particles with hundreds nanometer edge length - Zhang, Zhonghan (2018)
Self-assembly of polyhedral nanoparticles has identified as one of the key approaches towards bottom-up fabrication of novel functional materials. The process of spontaneous formation of ordered structures by thermodynamics and other constraints via energy lowering pathway has been intensively studied by the research community recently. Comparing to observation of final structures or limited in-situ detection, numerical simulations are valuable tools that revealing detailed dynamics information and relationship connecting microscopic structures and physical properties. Polyhedral particles with hundreds nanometer edge length (PPHEs) are promising candidates for large scale functional material assembly. More research efforts and understanding for their assembly process mechanism are required to enable practical applications. Nevertheless, utilizing PPHE assembly could be one of the next stages for advancement in nanomaterial fabrication. Reaching a comprehensive understanding for PPHE assembly process is intricate. This is understandable due to the complexity from both intrinsic properties and extrinsic environment for most nanoparticles systems, such as interaction description, material selection, and geometry. Among them, the large size scales of hundreds nanometer level, causes numerous problems in simulations. It is too large for molecular level simulations, yet too small to be described as bulk materials. We approached this problem by rediscovering their assembly mechanism in terms of interparticle interactions, surface modifications, and solvent-surfactant combinations. We have performed simulations that are reasonably representative to the nature of typical PPHE particles. The properties and parameters of the building blocks can be explicitly accessed for both inner core and outer surfactants. Then we investigated the contribution from different building blocks to the interparticle interactions. We found that for PPHEs, surface-induced interaction is still in dominant role for interparticle interaction but the size and surface-bulk ratio hinders fast response in dynamics. Tuning of interparticle interaction via controlling the surfactants and environment would cause significant changes in the thermodynamics of the assembly. Controlling parameter tests between different surface coating materials and solvents have been done for silver octahedra shaped PPHEs to plot phase diagram for assembled structure. This finding successfully relates the thermodynamic outcome of assembly with qualitative physical quantities of surfactant hydrophobicity and solvent polarity for PPHEs. Furthermore, experimental observations show good agreement with the simulation outputs, suggesting that quantitatively manipulation of the assembly outcome through changing attached surfactants and solvents could be possible. Lastly, in kinetic point of view, we utilized our previously developed methods to simulate the very initial stage of the assembly process. The whole work would serve as a preliminary attempt to exploit and connect the missing part between microscopic and macroscopic simulations.